Polypyrrole-Cl@poly(N-isopropylacrylamide) composite-based humidity and near infrared dual-response actuators. (6th April 2022) - Lv, Junping; Zhu, Lin; Zhang, Meng; Zhao, Zexu; Chen, Shu-Wei; Wang, Jinyi
Abstract: Actuators with controllable and reversible morphing towards environment stimuli have great potential applications in diverse fields. In spite of good progress made over the past decades, simple and efficient preparation of multi-response actuators is still a challenge. Here, we report a strategy to prepare humidity and near infrared (NIR) dual-response actuators with controllable and reversible bending or twisting deformation. The actuators were made up of two layers, one was polyvinyl butyral (PVB) layer with humidity and NIR inertness, and the other was chlorine-modified polypyrrole (PPy-Cl) doped poly(N-isopropylacrylamide-co-benzophenone) (PNIPAM-ABP) composite layer, taking advantage of the NIR photothermal conversion capability of PPy-Cl, along with the thermal-responsive PNIPAM-ABP. Upon NIR light irradiation, PPy-Cl converted light energy into heat, which subsequently induced the shrinkage of poly(N-isopropylacrylamide) (PNIPAM) chains; upon a high-humidity environment, PPy-Cl absorbed water molecular and transferred it into PNIPAM polymer, which further caused the bilayer to shrink or swell in an asymmetric manner, consequently leading to reversible bending or unbending behaviors. Interestingly, upon ultraviolet (UV) light irradiation with a grid photomask, the bilayer actuators showed bending or twist behaviors along with a special direction. The bionic flowers made from the actuators could imitate sunflower's opening and closing behaviors in response to NIR or humidity. The dual-response actuator could also imitate the lifting weight behaviors of forklifts. As an interesting example for potential utilization, a smart four-wheel vehicle was constructed using the bilayer actuator, showed excellent fast-moving performance. Graphical abstract: In this study, a strategy was developed for the fabrication of humidity and near infrared dual-response actuators by using PPy-Cl@poly(N-isopropylacrylamide) composite. Image 1 Highlights: PPy-Cl@poly(N-isopropylacrylamide) composite with humidity and near infrared responses was synthesized. A facile strategy for the preparation of humidity and near infrared dual-response actuators was developed. The actuator-based caterpillar-like robots had a high crawling speed of 0.12 mm/s under near infrared irradiation.